1990
DOI: 10.1128/jb.172.8.4161-4170.1990
|View full text |Cite
|
Sign up to set email alerts
|

Energy and calcium ion dependence of proteolysis during sporulation of Bacillus subtilis cells

Abstract: (12,27,35). Degradation of bulk protein during starvation is apparently a first-order process and yields a first-order rate constant of about 0.04 h-1 (22; our calculation).In growing Bacillus subtilis cells (4), rates of bulk protein degradation (1 to 3% h-1, depending on nutritional conditions) are similar to those seen in the enteric bacteria. In contrast, during the developmental process of spore formation, cells of the species Bacillus have been measured to degrade intracellular protein with first-order r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 46 publications
0
19
0
2
Order By: Relevance
“…In addition, protein degradation during sporulation of Bacillus subtilis has been reported to be a calcium-dependent process (O'Hara & Hageman, 1990), and in cyanobacteria it has long been recognized that there is a correlation between extracellular calcium concentration and heterocyst frequency (Smith & Wilkins, 1988;Zhao et al, 1991;Onek & Smith, 1992). However, our work represents probably the first example of continuous monitoring of [Ca 2+ ] i during a process of cell differentiation in a prokaryotic organism.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In addition, protein degradation during sporulation of Bacillus subtilis has been reported to be a calcium-dependent process (O'Hara & Hageman, 1990), and in cyanobacteria it has long been recognized that there is a correlation between extracellular calcium concentration and heterocyst frequency (Smith & Wilkins, 1988;Zhao et al, 1991;Onek & Smith, 1992). However, our work represents probably the first example of continuous monitoring of [Ca 2+ ] i during a process of cell differentiation in a prokaryotic organism.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore it is tempting to correlate the calcium transient with the signalling for proteolysis of phycobiliproteins. In fact, in B. subtilis a Ca 2+ influx has been shown to be essential for the early proteolysis that takes place during sporulation (O'Hara & Hageman, 1990;Shyu & Foegeding, 1991;Dominguez et al, 1999). However, the relevance of the calcium-dependent protease in the process of heterocyst differentiation remains unclear since Lockau et al (1988) and Maldener et al (1991) demonstrated that this protease is not essential for the development of functional heterocysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular alanine is probably generated during sporulation through the turnover of proteins. It has long been known that bulk protein turnover increases during sporulation (30,47,51). In addition, turnover of specific proteins is known to increase during sporulation (25,28,38,45).…”
Section: Resultsmentioning
confidence: 99%
“…The tricarboxylic acid cycle seems to play a role in the generation of energy during sporulation, as mutants that are defective in tricarboxylic acid cycle enzymes are defective in sporulation (13,18,56). Protein turnover is known to increase during sporulation (30,47) and probably plays a role in generating substrates (peptides and amino acids) for further metabolism and new macromolecular syn-thesis.…”
mentioning
confidence: 99%